The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1093/ajcn/61.5.1120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diets containing high or low amounts of stearic acid on plasma lipoprotein fractions and fecal fatty acid excretion of men

Abstract: Ten middle-aged males participated in a crossover study to determine the cholesterolemic effect of high amounts of stearic acid in a natural diet. They consumed a 20-d stabilization diet followed by two 40-d intervention diets containing either 1.5% of energy as stearic (18:0) acid and 7.3% of energy as palmitic (16:0) acid (low stearate: LS) or 2.4% of energy as 16:0 and 7.3% of energy as 18:0 (high stearate: HS). The experimental diets also contained approximately 10% of energy each as saturated and monounsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 22 publications
7
48
0
1
Order By: Relevance
“…This is in accordance with results published earlier by others (Tholstrup et al, 1994;Yu et al, 1995;Dougherty et al, 1995;Aro et al, 1997), who also found that when stearic acid is exchanged for C12±14 saturates, a moderate decrease in HDL-C was observed.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with results published earlier by others (Tholstrup et al, 1994;Yu et al, 1995;Dougherty et al, 1995;Aro et al, 1997), who also found that when stearic acid is exchanged for C12±14 saturates, a moderate decrease in HDL-C was observed.…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of fatty acids (free, soaps or derived from acylglycerols) of the total lipids has rarely been reported, but the fatty acid concentration in feces has been between 0.2 and 6 g/day (Bonanome and Grundy, 1988;Denke et al, 1993), typically 2-4 g/day (see e.g. Denke and Grundy, 1991;Dougherty et al, 1995;Snook et al, 1999). In the present study, crude fat excretion was at the expected level.…”
Section: Fecal Lipid Content and Compositionsupporting
confidence: 43%
“…The absorption of stearic acid from natural fats and oil is currently estimated to lie between 86 and 98% (Denke and Grundy, 1991;Dougherty et al, 1995;Baer et al, 2003). This is in conflict with the reported 63% absorption of stearic acid from Salatrim .…”
Section: Introductionmentioning
confidence: 91%
“…These results are consistent with data from Bonanome and Grundy (1988), Tholstrup et al (1994) and Kelly et al (2001), who demonstrated this decrease with greater calculated total dietary stearic acid intakes of 46 g, 58 g and 19.4 g per day, respectively. Tholstrup et al (1994), Dougherty et al (1995) and Kelly et al (2001) have previously reported a significant decrease in HDL cholesterol concentrations on high stearic acid diets (58, 23.6 and 19.4 g per day, respectively) compared with baseline.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequently, it was found that stearic acid was neutral in relation to plasma cholesterol changes (Hegsted et al, 1965;Keys et al, 1965). There are now a number of dietary studies which support the unique cholesterol-neutral properties of stearic acid (Kris-Etherton and Mustad, 1994;Tholstrup et al, 1994;Bonanome & Grundy, 1988), however the mechanisms behind this effect are not yet clear (Bonanome & Grundy, 1989;Kris-Etherton et al, 1993;Emken, 1994;Tholstrup et al, 1994;Dougherty et al, 1995;Rhee et al, 1997;Salter et al, 1998).…”
Section: Introductionmentioning
confidence: 99%